Tamanho de tumores da região selar como um preditor de perdas psicofísicas e eletrofisiológicas de campo visual - LOBÃO, Carlos Augusto Ferreira (Universidade Federal do Pará, 2024)
Sellar region tumor growth represents an important cause of visual loss due mechanical compression of the optic nerve apparatus. Many investigations have used non-invasive tools to evaluate the visual field consequences of this damage, and good association have been reported between psychophysical and electrophysiological perimetry. Few reports have considered the tumor size as predictor of the visual field loss. Objectives: In the present study, it was evaluated the association between tumor size and visual perimetry alterations measured by a psychophysical method, the Humphrey Visual Field Analyzer perimetry, and an electrophysiological method using the multifocal visual evoked cortical potential (mfVECP). Methods: The analyzed sample was composed by 14 patients diagnosed with sellar tumors on magnetic resonance imaging. The number of sectors with negative visual responses for both methods was counted. A simple logistic regression analysis was used to evaluate the association between the tumor dimensions and the visual field features. Results: Three patients had preserved visual fields, three patients showed hemianopic defects, and eight patients had generalized visual field losses at both evaluations. It was observed that the three maximum diameters of the tumor and total tumor volume had different predictive abilities regarding the extent of visual field loss when using psychophysical and mfVECP data. The maximum craniocaudal diameter of the tumor was the better predictor of the psychophysical measurements, while for mfVECP results, all tumor dimensions and volume had similar value to predict visual field losses. Conclusion: Sellar region tumor size is a predictor of visual loss found on psychophysical and electrophysiological visual perimetry. This correlation has potential to assist in the clinical intervention, and to prevent the irreversible visual impairment caused by these tumors to the patient.